The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1136/ard.62.6.576
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of symptomatic osteoarthritis in older adults: a population based study in Dicomano, Italy

Abstract: Objectives: To assess the prevalence of hand, hip, and knee osteoarthritis (OA) in an older Italian community dwelling population and its association with disability. Method: A cross sectional survey of the whole community aged 65 years and over, was carried out in Dicomano, a small rural town in Tuscany, Italy. Subjects were screened by geriatricians for major chronic conditions, including hip, knee, and hand OA, using diagnostic algorithms based on the American College of Rheumatology (ACR) clinical criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
82
1
14

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(103 citation statements)
references
References 10 publications
6
82
1
14
Order By: Relevance
“…Other studies have reported much higher rates of radiographic hip OA than symptomatic hip OA [22,37,43]. This suggests symptomatic hip OA confirmed by radiographic findings of hip OA according to an established method of diagnosis may be more relevant clinically than either method alone [40].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Other studies have reported much higher rates of radiographic hip OA than symptomatic hip OA [22,37,43]. This suggests symptomatic hip OA confirmed by radiographic findings of hip OA according to an established method of diagnosis may be more relevant clinically than either method alone [40].…”
Section: Discussionmentioning
confidence: 86%
“…Osteoarthritis (OA) is the most common rheumatic condition, the most frequent cause of musculoskeletal disability in developed countries, and one of the most common causes of disability resulting in limited activities of daily living in the general adult population [1,26,40]. Although OA may affect any joint in the body, it most commonly affects the knee followed closely by the hip [56].…”
Section: Introductionmentioning
confidence: 99%
“…OA of the knee accounts for more dependence in walking, stair climbing, and other lower-extremity tasks than any other disease (4,34,36,37). The data on 697 participants obtained from a cross-sectional survey carried out in Dicomano, Italy, showed that hip OA was strongly associated with disability in patients aged 65 years and more (38). According the data of a national survey carried out in France, more than 80% of all patients (n=10 412; mean age, 66.2 years) reported limitations in their ADL for basic tasks, leisure activities, or work.…”
Section: Impactmentioning
confidence: 99%
“…Moreover, Mannoni et al [4] have reported that hip OA is strongly associated with disability, and Hall et al [5] have reported that hip OA causes decreased physical functioning on the Western Ontario and McMaster Universities Osteoarthritis Index. Therefore, it is important to prevent hip OA progression via medical treatment.…”
Section: Introductionmentioning
confidence: 99%